The Period–Luminosity Relation of Long-period Variables in the Large Magellanic Cloud Observed with ATLAS - Daniel Hey; John Tonry; Benjamin Shappee; Daniel Huber (The Astrophysical Journal Supplement Series)
Period–luminosity (PL) relations of long-period variables (LPVs) are a powerful tool to map the distances of stars in our Galaxy, and are typically calibrated using stars in the Large Magellanic Cloud (LMC). Recent results demonstrated that these relations show a strong dependence on the amplitude of the variability, which can be used to greatly improve distance estimates. However, one of the only highly sampled catalogs of such variables in the LMC is based on Optical Gravitational Lensing Experiment photometry, which does not provide all-sky coverage. Here, we provide the first measurement of the PL relation of LPVs in the LMC using photometry from the Asteroid Terrestrial-impact Last Alert System (ATLAS). We derive conversions between ugriz , Gaia, and ATLAS c and o passbands with a precision of ∼0.02 mag, which enable the measurement of reliable amplitudes with ATLAS for crowded fields. We successfully reproduce the known PL sequences A through E, and show evidence for sequence F using the ratios of amplitudes observed in both ATLAS passbands. Our work demonstrates that the ATLAS survey can recover variability in evolved red giants and lays the foundation for an all-sky distance map of the Milky Way using LPVs.